Covert modality in non-finite contexts - Bhatt, Rajesh, 1973- (Interface explorations, 2006)
This book investigates the distribution and interpretation of Covert Modality. Covert Modality is modality which we interpret but which is not associated with any lexical item in the structure that we are interpreting. The book analyzes a class of environments that involves covert modality e.g. infinitival questions, infinitival relative clauses, purpose clauses, the 'have to' construction, and the 'is to' construction.